Insights from defining nurses' career success: An integrative review - Masako Yamada; Kyoko Asakura; Shoko Sugiyama; Nozomu Takada (Wiley, 2024)
Abstract Aims To review the literature and identify factors that make sense of and influence nurses' career success. We sought to provide insights into achieving nurses' career success. Design An integrative review conducted in May 2022 using Whittemore and Knafl's methodology of integrative review. Methods The databases searched were PubMed, Web of Science, Scopus, and CINAHL. Search criteria included the keywords "nurs*" and "career success" in the title and abstract. The quality of the reviewed papers was assessed using the JBI Critical Appraisal Tool for cross‐sectional studies and qualitative research. We extracted five types of information from quantitative studies: the definition of career success, factors of career success instruments, reliability or validity of career success instruments, and factors influencing nursing career success. Furthermore, we extracted two types of information from qualitative studies: themes that imply career success and factors that influence nurses' career success. Primary data were categorized into two perspectives: (1) what nurses' career success means and (2) what influences nurses' career success. Categorized data were unified into similar contents. Themes were developed from unified subgroups. Results Fourteen studies were included in the analysis. Seven themes were integrated into the factors that make sense of nurses' career success: satisfaction, positive attitude towards work, quality work in nursing, continuation of career and professional development, positive interaction at work, person-organization fit, and enrichment of an individual's life. Three themes were integrated into the factors influencing nursing career success: personal resources, positive behavior toward nursing work and research, and job resources and environment. No Patient or Public Contribution Patients or members of the public were not involved in this review.